Epoxide Opening versus Silica Condensation during Sol–Gel Hybrid Biomaterial Synthesis. Issue 24 (10th April 2013) - Gabrielli, Luca; Russo, Laura; Poveda, Ana; Jones, Julian R.; Nicotra, Francesco; Jiménez‐Barbero, Jesús; Cipolla, Laura
Abstract Hybrid organic–inorganic solids represent an important class of engineering materials, usually prepared by sol–gel processes by cross‐reaction between organic and inorganic precursors. The choice of the two components and control of the reaction conditions (especially pH value) allow the synthesis of hybrid materials with novel properties and functionalities. 3‐Glycidoxypropyltrimethoxysilane (GPTMS) is one of the most commonly used organic silanes for hybrid‐material fabrication. Herein, the reactivity of GPTMS in water at different pH values (pH 2–11) was deeply investigated for the first time by solution‐state multinuclear NMR spectroscopic and mass spectrometric analysis. The extent of the different and competing reactions that take place as a function of the pH value was elucidated. The NMR spectroscopic and mass spectrometric data clearly indicate that the pH value determines the kinetics of epoxide hydrolysis versus silicon condensation. Under slighly acidic conditions, the epoxy‐ring hydrolysis is kinetically more favourable than the formation of the silica network. In contrast, under basic conditions, silicon condensation is the main reaction that takes place. Full characterisation of the formed intermediates was carried out by using NMR spectroscopic and mass spectrometric analysis. These results indicate that strict control of the pH values allows tuning of the reactivity of the organic and inorganic moities, thus laying the foundations for the design and synthesis of sol–gel hybrid biomaterials with tuneable properties.